Classroom socialisation: repair and correction in Japanese as a heritage language. Issue 3 (3rd July 2021) - Burdelski, Matthew
ABSTRACT: This paper explores the classroom socialisation of a mundane institutional language policy regarding the use of the target language: Japanese. Based on audiovisual recordings in a Japanese as a heritage language (JHL) classroom, it analyses episodes when teachers initiated repair on children's novel English loanwords (i.e. English-based words pronounced in Japanese but not widely accepted and used), in ways that treated them (or sometimes the social actions performed through them) as problematic. Through a multimodal analysis of other-initiated repair turns and the sequences in which they were lodged, it examines how students responded, and whether and how teachers engaged in correction. In aiming to bridge research on classroom discourse using conversation analysis (CA) and language socialisation, the paper argues how repair and correction are practices for conveying the school language policy to 'speak only in Japanese'. It also argues that these practices have the potential for socialising students beyond the classroom, to membership into (an imagined) Japanese society where monitoring one's language use as a bilingual Japanese-English speaker may be important because the excessive use of English loanwords can become an object of others' negative attitudes and evaluations.